MILLING MACHINES TOOLS USED IN CAD-CAM TECHNOLOGY OF DENTAL PROSTHESES - Alexandru Andrei Iliescu; Paula Perlea; Mihaela Georgiana Iliescu; Irina Maria Gheorghiu (Romanian Society of Oral Rehabilitation, 2019)
Numerically controlled modern CAD-CAM milling machines tools dedicated to dental technology are kinematic structures that work in 4 or 5 axes and represent one of the key links of CAD-CAM technology flow. The 4-axis and 5-axis machines allow for superior quality of the milling surface integrity by controlling both the inclination of the feed angle and the direction of the milling guide on which depends the contact surface between the cutting tool and the workpiece. The milling tools are available for both dental offices and dental laboratories as well as for industrial dental laboratories. The CAD-CAM milling machines provide superior results to conventional methods in terms of mechanical strength in mastication and aesthetics of dental prostheses